2018
DOI: 10.1002/asia.201800729
|View full text |Cite
|
Sign up to set email alerts
|

Multiprotein Dynamic Combinatorial Chemistry: A Strategy for the Simultaneous Discovery of Subfamily‐Selective Inhibitors for Nucleic Acid Demethylases FTO and ALKBH3

Abstract: Dynamic combinatorial chemistry (DCC) is a powerful supramolecular approach for discovering ligands for biomolecules. To date, most, if not all, biologically templated DCC systems employ only a single biomolecule to direct the self-assembly process. To expand the scope of DCC, herein, a novel multiprotein DCC strategy has been developed that combines the discriminatory power of a zwitterionic "thermal tag" with the sensitivity of differential scanning fluorimetry. This strategy is highly sensitive and could di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 73 publications
0
42
0
Order By: Relevance
“…To assess the performance of our assay, a set of structurally-diverse small molecules ( Fig. 5a ) consisting of known FTO inhibitors (24PDCA, 50 LipotF, 25 Rhein, 24 IOX3 50 ) and non-inhibitor isonicotinic acid 40 were individually incubated at various concentrations with FTO (50 nM) and m 6 A-probe (10 μM) in a 384-well plate, and their fluorescence spectra simultaneously recorded on a fluorescence microplate reader. The inhibition curves are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess the performance of our assay, a set of structurally-diverse small molecules ( Fig. 5a ) consisting of known FTO inhibitors (24PDCA, 50 LipotF, 25 Rhein, 24 IOX3 50 ) and non-inhibitor isonicotinic acid 40 were individually incubated at various concentrations with FTO (50 nM) and m 6 A-probe (10 μM) in a 384-well plate, and their fluorescence spectra simultaneously recorded on a fluorescence microplate reader. The inhibition curves are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…By combining DSF with multiprotein dynamic combinatorial chemistry, Das et al developed an assay that simultaneously measures the melting temperatures of ALKBH3, ALKBH5, and FTO in dynamic chemistry libraries, which enabled the identification of selective inhibitors for FTO (with IC 50 = 2.6 μM) and ALKBH3. 70 …”
Section: Methods Of Screening Fto Inhibitorsmentioning
confidence: 99%
“…Later on, Svensen and Jaffrey reported an approach to identify FTO inhibitors by using a fluorometric RNA substrate based on broccoli aptamer [ 104 ]. Das and co-workers designed a multi-protein dynamic combinatorial chemistry (DCC) system for screening FTO inhibitors [ 105 ]. More recently, Zhang et al developed a single quantum dot-based Förster resonance energy transfer (FRET) nanosensor for FTO inhibitor screening [ 106 ].…”
Section: Inhibitorsmentioning
confidence: 99%
“…The molecule MO-I-500 displayed anticonvulsant activity in the 6 Hz mouse model at a nontoxic dose, increased the total m6A level of cellular RNA, and altered the production of relative microRNAs. Through using a multi-protein DCC strategy, compound 12 ( Figure 3 ) was identified as a FTO (IC 50 = 2.6 μM) selective inhibitor, in comparison with ALKBH5 (IC 50 = 201.3 μM) [ 105 ]. The structural model of FTO- 12 revealed that compound 12 coordinated with Fe 2+ in a bidentate manner, which was further stabilized by a combination of hydrogen-bonding and salt bridge interactions with Arg96, Arg319, Tyr295, and Ser318 of side chains from FTO.…”
Section: Inhibitorsmentioning
confidence: 99%